Δ56Fe in seabird guano reveals extensive recycling of iron in the Southern Ocean ecosystem. (26th March 2017) - Wing, S. R.; Gault‐Ringold, M.; Stirling, C. H.; Wing, L. C.; Shatova, O. A.; Frew, R. D.
Abstract: Availability of iron limits productivity in the Southern Ocean where vast regions of high‐nitrogen low‐chlorophyll conditions are punctuated by hotspots of production surrounding the subAntarctic islands. Here, we compare patterns in accumulation of iron, as indicated by [Fe] and Fe : C (from Wing et al.2014 ), with proxies for uptake of iron within food webs, as indicated by Fe : Al and δ 56 Fe within the subAntarctic Auckland Island ecosystem. We compare these proxies for dynamics of iron within egested material collected from six seabird species, representing three distinct foraging guilds. Fractions of biogenic iron, estimated from Fe : Al, were lowest in the coastal foraging guild (0.83 ± 0.01), and higher in the oceanic and predator guilds (0.94 ± 0.01 and 0.95 ± 0.01), consistent with high rates of biological recycling. The isotopic ratio of iron 56 Fe/ 54 Fe, reported as δ 56 Fe, is depleted in the heavy isotope 56 Fe by recycling in the microbial loop, and is likely further depleted in 56 Fe when taken up by animals within the food web. δ 56 Fe was most negative for the oceanic foraging group indicating intensive recycling (−1.16 ± 0.16‰), most positive in the coastal group where direct lithogenic sources of iron are more available (−0.14 ± 0.15‰), and intermediate in the predatory group, representing a mixture and possible fractionation within food webs (−0.37 ± 0.14‰). These data reveal strong contrasts in bioaccumulation and recycling of iron between coastal and oceanic food webs, and important interactions between marine food web structure and biogeochemical processes supporting productivity in the Southern Ocean.